Regulation of Personal Data Legal Protection in BPJS Ketenagakerjaan Membership, Denpasar Branch Office - Saifullah Hasan; AAA. Ngurah Sri Rahayu Gorda (Green Publisher Indonesia, 2025)
This research analyzes legal protection arrangements for personal data in BPJS Ketenagakerjaan Denpasar Branch membership and examines the institution's responsibilities in safeguarding participants’ information. Employing normative juridical methods with statute, comparative, conceptual, and economic law analysis, it draws on secondary legal materials from primary, secondary, and tertiary sources. Findings indicate that personal data protection in BPJS Ketenagakerjaan is governed by Law Number 27 of 2022 on Personal Data Protection and Law Number 24 of 2011 concerning the Social Security Administering Body. As data controller, BPJS Ketenagakerjaan must ensure legitimacy, confidentiality, and security via internal policies, encryption, restricted access, and audits. Yet, the Denpasar Branch faces challenges like limited human resources, low participant awareness, and risks of misuse or cyberattacks. Stronger internal oversight, staff capacity building, and inter-institutional synergy are essential for effective implementation aligned with legal certainty, justice, and human rights. Recommendations include regular security audits, comprehensive data privacy training, clear incident protocols, educational campaigns on data rights, and advanced cybersecurity like multi-factor authentication and real-time monitoring.